Predicting Intra-Day and Day of the Week Anomalies in Turkish Stock Market - Kemal Eyuboglu; Sinem Eyuboglu; Rahmi Yamak (Romanian Economic Journal, 2016)
According to Efficient Market Hypothesis, investors cannot gain abnormal returns. But various anomalies such as day or intra-day effect which are frequently observed at the stock markets provide some abnormal returns to investors. In the literature, many studies have found various anomalies for different national and international stock markets. But most of the applied studies used aggregate data in their econometric analysis. The question is whether the same anomalies exist in sub-indexes such as communication, technology, sports and services, etc. The purpose of this study is to investigate whether there are the same anomalies such as intra-day effect and day of the week effect for an aggregated index and 23 sub-indexes of Borsa Istanbul. The data which used in this study is daily and covers the period of 2005-2015 for Turkey. Findings show that there is evidence for intra-day effect in all 24 indexes and day of the week effect in 2 sub-indexes.